Implementation of Occupational Safety and Health Aspects Aboard Purse Seiner - Asva, Achmadil Razaq; Perangin-angin, Robet; Harisjon, Harisjon (PELAGICUS, 2023)
Fishing technically represents one of the activities at sea that is classified as having a higher risk or level of danger than other work on land. According to the Minister of Manpower Regulation Number 26 of 2014, every company must implement occupational safety and health standards starting from the management, employers, and all workers as a unit in a company, so that indirectly companies are required to be able to provide an understanding of occupational safety and health competencies. , to improve the work safety system. This research aims to determine the implementation of occupational safety and health aspects on the Purse Seine Ship. Aspects of occupational safety on purse seine vessels, consisting of firstly the application of occupational safety and health aspects when operating fishing gear, which are still not implemented well, and secondly the application of occupational safety and health aspects when handling catches, which are not yet complete and do not comply with established standards. has been established. Referring to the International Convention for the Safety of Life at Sea (SOLAS), 1974, the completeness of work safety equipment on purse seine ships still does not meet the specified equipment standards. For this reason, the Government must play a role in ensuring the implementation of work safety standards on fishing vessels, especially purse seine vessels.